GAMBARAN KONDISI SANITASI LINGKUNGAN RUMAH DENGAN KEJADIAN DIARE PADA BALITA DI WILAYAH KERJA PUSKESMAS BUAYAN KABUPATEN KEBUMEN - Minanda Oktariza; Suhartono Suhartono; Dharminto Dharminto (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
Diarrhea is still the leading cause of death among toodler in Indonesia. Puskesmas Buayan is the working area with the discovery of the highest case of diarrhea in Kebumen regency in 2016, and in 2017 with 729 cases for diarrhea in toodler. Low environmental sanitation conditions become one of the dominant factors causing diarrhea. The purpose of this research is to know the relation of environmental sanitation condition of house with diarrhea occurrence at toddler in working area of Puskesmas Buayan Kebumen. This research use cross sectional approach with 68 samples. The results showed that there were 39.7% of underfives suffering from diarrhea with unsafe drinking water source 52,9%, clean water supply did not fulfill requirement 33,8%, latrine condition did not fulfill requirement 23,5%, condition of garbage dump not qualified 47.1% and SPAL conditions did not meet the requirements 57.4%. The result of bivariate analysis shows that drinking water source has p-value=0,919, clean water supply p-value =0,037, latrine condition p-value=0,015, garbage dump condition p-value=0,060, and SPAL condition p-value=0,012. It can be concluded that there is a significant correlation between clean water supply, latrine condition and SPAL condition with diarrhea occurrence in toddler in Puskesmas Buayan Kebumen.